Replication-Competent ΔNS1 Influenza A Viruses Expressing Reporter Genes - Aitor Nogales (Viruses, 2021)
The influenza A virus (IAV) is able to infect multiple mammalian and avian species, and in humans IAV is responsible for annual seasonal epidemics and occasional pandemics of respiratory disease with significant health and economic impacts. Studying IAV involves laborious secondary methodologies to identify infected cells. Therefore, to circumvent this requirement, in recent years, multiple replication-competent infectious IAV expressing traceable reporter genes have been developed. These IAVs have been very useful for in vitro and/or in vivo studies of viral replication, identification of neutralizing antibodies or antivirals, and in studies to evaluate vaccine efficacy, among others. In this report, we describe, for the first time, the generation and characterization of two replication-competent influenza A/Puerto Rico/8/1934 H1N1 (PR8) viruses where the viral non-structural protein 1 (NS1) was substituted by the monomeric (m)Cherry fluorescent or the NanoLuc luciferase (Nluc) proteins. The ΔNS1 mCherry was able to replicate in cultured cells and in Signal Transducer and Activator of Transcription 1 (STAT1) deficient mice, although at a lower extent than a wild-type (WT) PR8 virus expressing the same mCherry fluorescent protein (WT mCherry). Notably, expression of either reporter gene (mCherry or Nluc) was detected in infected cells by fluorescent microscopy or luciferase plate readers, respectively. ΔNS1 IAV expressing reporter genes provide a novel approach to better understand the biology and pathogenesis of IAV, and represent an excellent tool to develop new therapeutic approaches against IAV infections.